Ultrafiltrasi, Hidroponik Vertikal, dan Literasi Digital di Desa Sungai Bangkal - Farah Hafizha; Redhana Aulia; Isnaniah; Aulia Nur, Annisa; Nur Ad’ha Yuda; Mina Azahra (Jurnal Inovasi Pengabdian Masyarakat, 2026)
This community service program aimed to improve the quality of life in Sungai Bangkal Village by integrating appropriate technologies for clean water, household food security, and digital capacity building. The program was implemented from 9 October to 18 December 2025 using a participatory approach with two main partners: a Farmer Group and a Community Health Post (Posyandu). Interventions included constructing a filtration house and installing an ultrafiltration unit, introducing vertical hydroponics for limited land, and training participants to use spreadsheets for administrative and financial recording. Field-based simple tests indicated a reduction in water turbidity of approximately 90%, while hydroponic cultivation achieved about 80% plant survival to the early harvest stage. Pre–post evaluation among 20 Farmer Group respondents showed marked improvements in record-keeping (0–75), management understanding (25–85), clean-water SOP development (0–90), business planning (0–80), technical team formation (0–95), and management capability (25–85). Among 20 Posyandu respondents, average knowledge increased by 61.6%, particularly regarding the clean water–nutrition–stunting nexus and healthy-living practices. The program strengthened cross-group collaboration and data-driven sustainability